Integrating disaster literacy in high school geography: Designing and testing a flood assessment tool - Mohamad Tusam; Lili Somantri; Iwan Setiawan (Research and Development in Education (RaDEn), 2024)
Indonesia's high vulnerability to flood disasters has significant social and educational impacts, especially on secondary school students. This research addresses the need for an effective flood disaster literacy tool by developing a credible and validated test instrument designed for high school geography education. Using the ADDIE model, this research involved the stages of review, creation, implementation, testing, and assessment. The study involved a sample of 30 students from SMA Negeri 1 Beber, Cirebon Regency, who were assessed for their understanding through a specially designed flood disaster literacy test. The results showed a mix of correct and incorrect answers, with notable variations in students' understanding. The test instrument showed high validity and reliability, with a KR-21 coefficient of 0.963, confirming its robustness. Despite a few invalid items, the instrument effectively evaluated key aspects of flood disaster literacy, including knowledge, attitudes and practical skills. The findings highlight strengths and areas for improvement in students' understanding, emphasising the need for targeted educational strategies. This research contributes to improving geography education by integrating disaster literacy and offers a foundation for future curriculum development.